EVALUASI MANAJEMEN PROYEK - Suryanto, Suryanto; Gondodiyoto, Sanyoto; I, Desi N; Aryanto, Aryanto; Triana, Elis (Bina Nusantara University, 2009)
The purpose of this study was to evaluate the project management and make suggestions to the problems being faced by the company. Many companies or individuals working on a project basis (project based), but many of those who do not manage the project well, even with no management at all and let the project flow as it is. Therefore, it needs a proper guidance and methods to support a project management information system. The research method used is the method of data collection, covering literature from books, articles from the internet, and study the documentation to PT ACM through direct interviews with the parties concerned with the project. The data analysis technique used is based on the 9 knowledge areas and 5 stages in project management. The results are the company’s project is proposed to be closed (closing) so as not to increase corporate spending on the project. The conclusion of this scientific work is a project run by the 2 parties have a higher risk of failure.Keywords: evaluation, management, project